Artists' Statements. - Taube, Heinrich; Cole, Tim; Cole, Pete; Eacott, John; Angliss, Sarah; Miranda, Eduardo Reck; McLeran, Aaron; Akamatsu, Masayuki; Alexander, Amy; Cope, David; Pearce, Marcus (Contemporary Music Review, 2009)
This article presents views of several artists on the emergence of generative music. Heinrich Taube identifies a number of motivations that lead him to work with generative musical processes. John Eacott discusses his observation that the majority of music audiences are probably unaware of the use of generative processes despite the significant numbers of musicians and technologists investigating them. Meanwhile, Eduardo Reck Miranda addresses the practice of algorithmic composition on many occasions.